Novel risk scores for survival and intracranial failure in patients treated with radiosurgery alone to melanoma brain metastases. Issue 1 (December 2015) - Chowdhury, Imran; Ojerholm, Eric; McMillan, Matthew; Miller, Denise; Kolker, James; Kurtz, Goldie; Dorsey, Jay; Nagda, Suneel; Geiger, Geoffrey; Brem, Steven; O'Rourke, Donald; Zager, Eric; et al.
Abstract Purpose Stereotactic radiosurgery (SRS) alone is an increasingly common treatment strategy for brain metastases. However, existing prognostic tools for overall survival (OS) were developed using cohorts of patients treated predominantly with approaches other than SRS alone. Therefore, we devised novel risk scores for OS and distant brain failure (DF) for melanoma brain metastases (MBM) treated with SRS alone. Methods and materials We retrospectively reviewed 86 patients treated with SRS alone for MBM from 2009-2014. OS and DF were estimated using the Kaplan-Meier method. Cox proportional hazards modeling identified clinical risk factors. Risk scores were created based on weighted regression coefficients. OS scores range from 0-10 (0 representing best OS), and DF risk scores range from 0-5 (0 representing lowest risk of DF). Predictive power was evaluated using c-index statistics. Bootstrapping with 200 resamples tested model stability. Results The median OS was 8.1 months from SRS, and 54 (70.1 %) patients had DF at a median of 3.3 months. Risk scores for OS were predicated on performance status, extracranial disease (ED) status, number of lesions, and gender. Median OS for the low-risk group (0-3 points) was not reached. For the moderate-risk (4-6 points) and high-risk (6.5-10) groups, median OS was 7.6 months and 2.4 months, respectively (p < .0001). Scores for DF were predicated on performance status, ED status, and number of lesions. Median time to DF for the low-risk group (0 points) was not reached. For the moderate-risk (1-2 points) and high-risk (3-5 points) groups, time to DF was 4.8 and 2.0 months, respectively (p < .0001). The novel scores were more predictive (c-index = 0.72) than melanoma-specific graded prognostic assessment or RTOG recursive partitioning analysis tools (c-index = 0.66 and 0.57, respectively). Conclusions We devised novel risk scores for MBM treated with SRS alone. These scores have implications for prognosis and treatment strategy selection (SRS versus whole-brain radiotherapy).